(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was conducted to determine the prevalence of clinical diseases and disorders in goats at Jhenaidah Sadar upazilla, Jhenaidah, Bangladesh. A total of 120 sick goats were examined during the period from September to November, 2015. The presumptive diagnosis of the diseases was performed on the basis of history, owner’s complaints, clinical findings and physical examination of patients. Among the diseases and disorders, parasitic infestation 34 (28.33%) case were highest in all cases. On the other hand, non specific fever 25 (20.83%), anorexia 14 (11.67%), peste des petits ruminants (PPR) 10 (8.33%), Gid disease 3 (2.5%), Diarrhea 5(4.17%), Myiasis wound 7(5.83%), Bloat 4(3.33%), Navel ill 2(1.67%), Pneumonia 7(5.83%), Vitamin and mineral deficiency 4(3.33%) and Dystocia 5(4.17%) were also recorded. It was also reported that adult (62.5%), female (66.67%) and Black Bengal goats (89.16%) were showed more susceptible to diseases than young (37.5%), male (33.33%) and Jamunapari (10.83%) goats. These results of the study might be helpful to develop effective prevention and control strategies against diseases and disorders in goats. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 45-50